Pharmacokinetics and tolerability of paliperidone palmitate injection in Chinese subjects. (March 2014) - Si, Tianmei; Su, Yun'ai; Liu, Yi; Zhang, Hongyan; Li, Huafang; Rui, Qing; Shu, Liang
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to characterize the pharmacokinetics of 25, 100, and 150 mg equivalents (eq.) of paliperidone long‐acting injection in Chinese subjects with schizophrenia. Methods This was an open‐label, randomized, parallel group, multicenter study. A total of 48 patients were randomized in a 1:1:1 ratio to one of three groups. Sequential blood samples were collected immediately before injection on day 1 and up to 210 days after the first injection. The plasma paliperidone concentrations were determined by a validated high‐performance liquid chromatography/tandem mass spectrometry method. Results A total of 47 patients received at least one injection of the study medication, and 43 completed the study. The pharmacokinetic (PK) parameters, such as time to maximum concentration, t1/2, and CL/F, were comparable across the three treatment groups (p = 0.935, 0.349, and 0.794, respectively). The differences in maximum plasma concentration, AUC (035 days), AUC (0–210 days), and AUC (0–∞) were significant (p < 0.001) and dose proportional. The inter‐individual variation of PK parameters was large. The most frequent treatment‐emergent adverse events were prolactin level increasing, injection site pain, tremor, dry mouth, and constipation. Conclusions The pharmacokinetics of paliperidone palmitate are linear with respect to time in Chinese subjects with schizophrenia at injections from 25 to 150 mg eq. Copyright © 2014 John Wiley & Sons, Ltd.